Protective effect of Matricaria Chamomilla extract on hepatic-renal toxicity of ceftriaxone in rats - Farouk, Mona; Abokora, Seham; Ali, Abdel-Fatah (International Journal of Pharmacology and Toxicology, 2017)
The effect of Matricaria chamomilla (M.chamomilla) against hepatic-renal toxicity of Ceftriaxone was investigated in this study. Twenty eight rats were divided into four groups. The 1st group was injected with saline as control, the 2nd  and 3rd  groups were injected with M.chamomilla extraction ( 50mg/kg.b.wt) and with ceftriaxone ( 180 mg/kg.b.wt.) for two and one week respectively while the 4th  group was injected with M.chamomilla extraction plus ceftriaxone. at dose 50mg/kg and 180 mg/kg.b.wt respectively ,daily for the one week and with M.chamomilla extraction only at dose 50mg/kg.b.wt for another week. At the end of the 1st  week, the 3rd group had significantly higher ALP,ALT,AST, urea and creatinine levels with significantly lower albumin and A/G ratio levels than that of the 1st and 2nd groups , while the 4th  group did not differ from 1st and 2nd groups in terms of these parameters. Histopathological studies revealed that, the 3rd  group had some pathological changes in the liver and kidney.From this study we can conclude that, M. chamomilla extraction  can reduce hepatic-renal toxicity of ceftriaxone in rats.